Targeting Brain Drug Delivery with Macromolecules Through Receptor-Mediated Transcytosis - Yuanke Li; Ruiying Liu; Zhen Zhao (Pharmaceutics)
Brain diseases pose significant treatment challenges due to the restrictive nature of the blood–brain barrier (BBB). Recent advances in targeting macromolecules offer promising avenues for overcoming these obstacles through receptor-mediated transcytosis (RMT). We summarize the current progress in targeting brain drug delivery with macromolecules for brain diseases. This exploration details the transport mechanisms across the BBB, focusing on RMT and its use of natural ligands for drug delivery. Furthermore, the review examines macromolecular ligands such as antibodies, peptides, and aptamers that leverage RMT for effective BBB traversal. Advancements in macromolecules-based delivery systems for brain diseases are summarized, emphasizing their therapeutic potential and limitations. Finally, emerging RMT strategies, including viral vectors, exosomes, and boron neutron capture therapy, are discussed for their precision in brain-targeted treatments. This comprehensive overview underscores the potential of RMT-based approaches to revolutionize brain disease therapy.